The effect of posture regulation training on musculoskeletal disorders, fatigue level and job performance in intensive care nurses - Oguzhan Bahadir Demir; Feride Taskin Yilmaz (BMC, 2024)
Abstract Background Intensive care units (ICUs) are one of the high-risk working areas in terms of musculoskeletal disability and ergonomic risks including the environment and posture factors. Correct posture technique is often ignored by nurses working in these units. This study was conducted to determine the effect of posture regulation training on work-related musculoskeletal disorders, fatigue level and job performance in nurses working in ICUs. Methods This quasi-experimental study with one-group pretest-posttest design included 64 intensive care nurses. The nurses received posture regulation training in three different sessions. The post-test was administered four months after the posture regulation training. Results The nurses reported to frequently have aches, pains and discomfort in the neck, upper back and lumbar regions. After the posture regulation training, their level of pain, ache and discomfort in the neck, right and left shoulder, upper back, lower back and right/left foot areas decreased significantly (p < 0.05). The posture regulation training reduced the levels of behavior/severity and affect, which are sub-dimensions of fatigue, and increased the level of contribution to work, which is a sub-dimension of job performance (p < 0.05). Conclusion The posture regulation training decreased the level of symptoms in the neck, shoulder, upper back, lower back and foot regions of intensive care nurses and partially improved their fatigue level and job performance. Therefore, posture regulation training should be added to in-service training programs and permanent measures should be taken for ergonomic risks in ICUs.